2021
DOI: 10.5194/egusphere-egu21-16174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifractal and joint multifractal analysis of the spatial variability of CO2 emission and other soil properties

Abstract: <p>Soil is a major source and also a sink of CO<sub>2</sub>. Agricultural management practices influence soil  carbon sequestration. Identification of CO<sub>2</sub> emission hotspots may be instrumental in implemented strategies for managing carbon cycling in agricultural soils. We used multifractal analysis to assess the spatial variability of both, soil CO<sub>2</sub> emissions and associated soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Analyzing high-frequency time series of air measurements, Karatasou and Santamouris [8] applied power spectral density analysis over time scales and found that air temperature data exhibit turbulent-like intermittent properties with multifractal statistics. Multifractal nature has not spared the soil CO 2 emissions and selected soil attributes: soil water content, temperature, clay content, macro and microporosity, air-free porosity, magnetic susceptibility, bulk density, humification index of soil organic matter, and relative to organic carbon content [20]. EU carbon market also demonstrates multifractality [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analyzing high-frequency time series of air measurements, Karatasou and Santamouris [8] applied power spectral density analysis over time scales and found that air temperature data exhibit turbulent-like intermittent properties with multifractal statistics. Multifractal nature has not spared the soil CO 2 emissions and selected soil attributes: soil water content, temperature, clay content, macro and microporosity, air-free porosity, magnetic susceptibility, bulk density, humification index of soil organic matter, and relative to organic carbon content [20]. EU carbon market also demonstrates multifractality [13].…”
Section: Literature Reviewmentioning
confidence: 99%